2016
DOI: 10.1371/journal.pone.0158344
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy Corrects Mitochondrial Dysfunction in Hematopoietic Progenitor Cells and Fibroblasts from Coq9R239X Mice

Abstract: Recent clinical trials have shown that in vivo and ex vivo gene therapy strategies can be an option for the treatment of several neurological disorders. Both strategies require efficient and safe vectors to 1) deliver the therapeutic gene directly into the CNS or 2) to genetically modify stem cells that will be used as Trojan horses for the systemic delivery of the therapeutic protein. A group of target diseases for these therapeutic strategies are mitochondrial encephalopathies due to mutations in nuclear DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…The connection between CoQ levels and bioenergetics defects has also been demonstrated in conditions of pharmacological inhibition of CoQ biosynthesis in human skin fibroblasts and neurons [ 15 ]. Also, mouse embryonic fibroblasts (MEFs) from a Coq7 knockout mouse model or a Coq9 knock-in mouse model ( Coq9 R239X ), generated by independent groups, show a reduction in mitochondrial respiration and a decrease in ATP production [ 42 , 43 , 44 , 45 ]. COQ7 is a hydroxylase that uses demethoxyubiquinone (DMQ) as substrate in the CoQ biosynthetic pathway, and it needs COQ9 for its stability and function [ 2 , 3 , 44 ].…”
Section: Coq In the Oxphos Systemmentioning
confidence: 99%
“…The connection between CoQ levels and bioenergetics defects has also been demonstrated in conditions of pharmacological inhibition of CoQ biosynthesis in human skin fibroblasts and neurons [ 15 ]. Also, mouse embryonic fibroblasts (MEFs) from a Coq7 knockout mouse model or a Coq9 knock-in mouse model ( Coq9 R239X ), generated by independent groups, show a reduction in mitochondrial respiration and a decrease in ATP production [ 42 , 43 , 44 , 45 ]. COQ7 is a hydroxylase that uses demethoxyubiquinone (DMQ) as substrate in the CoQ biosynthetic pathway, and it needs COQ9 for its stability and function [ 2 , 3 , 44 ].…”
Section: Coq In the Oxphos Systemmentioning
confidence: 99%
“…Two other therapeutic strategies have been tested using the Coq9 R239X mouse model or cells from this mouse model. Firstly, the use of a lentiviral vector (CCoq9WP) allowed the ectopi over-expression of Coq9 in mouse embryonic fibroblasts (MEFs) and hematopoietic progenitor cells (HPC), leading to the restore of the CoQ biosynthetic pathway and mitochondrial function [ 122 ]. Secondly, researchers tested the therapeutic effects of rapamycin administration in Coq9 R239X mice [ 153 ] based on other studies that had demonstrated the therapeutic benefits of rapamycin therapy in a few mouse models of mitochondrial diseases [ 154 , 155 ].…”
Section: Vertebrate Models Of Coq Deficiencymentioning
confidence: 99%